Fostering environmental stewardship among university students - design recommendation for a student plaza at the Faculty Of Sustainable Agriculture, UMS Sandakan - Teo, Chrissy,Ye En (Faculty Of Sustainable Agriculture, 2016)
A study was conducted at the land next to student hostel Block A in Faculty of Sustainable Agriculture (FSA), Universiti Malaysia Sabah. This study was aimed to cdesign a student plaza in the faculty which able to encourage environmental stewardship and promote social interaction among the university students. The objectives of this study were to assess the input of the faculty's community on the idea of a successful plaza in FSA, to conduct site inventory and analysis at the proposed site and to recommend a plaza design which encourages social interaction and environmental stewardship among the community. In this study, mixed method approach (questionnaire survey and site inventory and analysis) was used to collect data. The questionnaire survey was distributed to SO respondents of FSA to evaluate their opinions towards landscape based on the concept of 'Placemaking'. The data from the survey was analyzed by calculating and determining the frequency (N) and percentage (%) of respondents. Site inventory and site analysis was carried out in order to collect and evaluate the data from the site. The collected data from the site inventory and analysis was recorded and displayed in table form. The recommendation design plan was displayed through the use of Master plan, Elevation plan, Perspective drawing and Planting Palette. Based on the survey, it was found that the students in FSA have high environmental awareness. They preferred to do environmental activities such as edible gardening and collaborative maintenance in order to develop proenvironmental behaviours. The design of the student plaza was based on the survey under the theme of community living room. The plaza was divided into four main areas; auditorium, edible garden, discussion area and outdoor gymnasium. All these four areas were aimed to promote sociability and environmental stewardship among the students. The vegetation in this plaza design was recommended through the use of planting pallete. All the vegetation possessed herbal properties which able to relax and refresh the students' minds. Another sustainable practice that can be found in this design is the materials used to build hardscapes wiJI be reclaimed materials such as woods and bricks. Permeable paving was also another sustainable practice in this design. Insufficient of time, lack of facilities for landscape research and language constraint were the limitations that can be found in this study.